2011
DOI: 10.2514/1.j050683
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Vortex Generators in a Navier-Stokes Code

Abstract: A source-term model that simulates the effects of vortex generators was implemented into the Wind-US NavierStokes code. The source term added to the Navier-Stokes equations simulates the lift force that would result from a vane-type vortex generator in the flowfield. The implementation is user-friendly, requiring the user to specify only three quantities for each desired vortex generator: the range of grid points over which the force is to be applied and the planform area and angle of incidence of the physical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(17 citation statements)
references
References 13 publications
(26 reference statements)
1
13
0
Order By: Relevance
“…The source term modeling is known as the BAY model in Wind-US. 8 The BAY model has been applied for vane-type vortex generators within subsonic and supersonic flows. 8 The BAY model does not account for the viscous forces on the vanes, and so, the losses in total pressure due to the vanes are not modeled.…”
Section: B Source Term Vortex Generator Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The source term modeling is known as the BAY model in Wind-US. 8 The BAY model has been applied for vane-type vortex generators within subsonic and supersonic flows. 8 The BAY model does not account for the viscous forces on the vanes, and so, the losses in total pressure due to the vanes are not modeled.…”
Section: B Source Term Vortex Generator Modelmentioning
confidence: 99%
“…8 The BAY model has been applied for vane-type vortex generators within subsonic and supersonic flows. 8 The BAY model does not account for the viscous forces on the vanes, and so, the losses in total pressure due to the vanes are not modeled. The inputs to the BAY model include the grid range that would contain the vane, the angle-of-incidence of the vane, and the planform area of the vane.…”
Section: B Source Term Vortex Generator Modelmentioning
confidence: 99%
“…20,21 The model mimics the effect of VGs on the flow by approximately enforcing flow tangency in a group of cells in the vicinity of the VG location. This is achieved using local source terms in the momentum equation of the form…”
Section: The Bay and Jbay Modelsmentioning
confidence: 99%
“…A few approaches to the design of such a body force are available in the literature (see, e.g., [18][19][20][21][22][23]). In this study, we use a simple approach that is based on the direct numerical simulation study of Liu et al [23] and was shown to be robust and quite accurate within SARC SRANS computations in [24].…”
Section: Representation Of Vortex Generators By a Body Forcementioning
confidence: 99%